Call the midwife. Season twelve [videorecording (DVD)] - Thomas, Heidi, 1962- (Call the midwife [DVD videorecording], 2023)
It's 1968 and Enoch Powell's infamous 'Rivers of Blood' speech creates serious tension in Poplar, especially when a group of dockers march in support of Powell. The midwives welcome a new nun, Sister Veronica, who's an instant hit with everyone, except Nurse Crane. Meanwhile, Trixie's relationship with Matthew goes from strength to strength, while Nurse Crane helps Nancy with her financial woes. Sister Julienne enjoys helping out on the district rounds, Shelagh and Dr. Turner split their time between the busy maternity home and their lively young family, while Reggie continues to bring joy into Violet and Fred's lives.